Parental Age in Relation to Offspring's Neurodevelopment. Issue 5 (3rd September 2021) - Veldkamp, S. A. M.; Zondervan-Zwijnenburg, M. A. J.; van Bergen, Elsje; Barzeva, S. A.; Tamayo-Martinez, N.; Becht, A. I.; van Beijsterveldt, C. E. M.; Meeus, W.; Branje, S.; Hillegers, M. H. J.; Oldehinkel, A. J.; Hoijtink, H. J. A.; et al.
ABSTRACT: Objective : Advanced parenthood increases the risk of severe neurodevelopmental disorders like autism, Down syndrome and schizophrenia. Does advanced parenthood also negatively impact offspring's general neurodevelopment? Method : We analyzed child-, father-, mother- and teacher-rated attention-problems ( N = 38, 024), and standardized measures of intelligence ( N = 10, 273) and educational achievement ( N = 17, 522) of children from four Dutch population-based cohorts. The mean age over cohorts varied from 9.73–13.03. Most participants were of Dutch origin, ranging from 58.7%-96.7% over cohorts. We analyzed 50% of the data to generate hypotheses and the other 50% to evaluate support for these hypotheses. We aggregated the results over cohorts with Bayesian research synthesis. Results : We mostly found negative linear relations between parental age and attention-problems, meaning that offspring of younger parents tended to have more attention problems. Maternal age was positively and linearly related to offspring's IQ and educational achievement. Paternal age showed an attenuating positive relation with educational achievement and an inverted U-shape relation with IQ, with offspring of younger and older fathers at a disadvantage. Only the associations with maternal age remained after including SES. The inclusion of child gender in the model did not affect the relation between parental age and the study outcomes. Conclusions : Effects were small but significant, with better outcomes for children born to older parents. Older parents tended to be of higher SES. Indeed, the positive relation between parental age and offspring neurodevelopmental outcomes was partly confounded by SES.